1998
DOI: 10.1093/jn/128.8.1253
|View full text |Cite
|
Sign up to set email alerts
|

Experiment Station Dietary Studies Prior to World War II: A Bibliography for the Study of Changing American Food Habits and Diet Over Time

Abstract: Dietaries reported by previous generations of researchers, originally collected to advance the science of human nutrition, now have considerable value as primary historical documents. USDA experiment station reports and bulletins represent the single largest collection of such documents. Our annotated bibliography of experiment station studies is meant to facilitate their use in historical and other diachronic studies of American food habits and diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…For example, one study linked the intake of dairy products to dental health (Morey 1933) while others identified the importance of good nutrition for disease prevention (Moser 1935a;Stiebeling 1930). In the general area of diet and nutrition, there were 32 experiment station bulletins published between 1926 and 1930 (Dirks and Duran 1998). In the 1950s, the emphasis on nutrition, food storage, and time-saving food production strategies (e.g., meal planning) continued to grow (Moser 1953;Swan 1986).…”
Section: Background On Diet and Homemakers' Time Usementioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study linked the intake of dairy products to dental health (Morey 1933) while others identified the importance of good nutrition for disease prevention (Moser 1935a;Stiebeling 1930). In the general area of diet and nutrition, there were 32 experiment station bulletins published between 1926 and 1930 (Dirks and Duran 1998). In the 1950s, the emphasis on nutrition, food storage, and time-saving food production strategies (e.g., meal planning) continued to grow (Moser 1953;Swan 1986).…”
Section: Background On Diet and Homemakers' Time Usementioning
confidence: 99%
“…This food rule implies it could be insightful to trace dietary changes back in time at least 60 to 80 years if we are to understand how they may be underpinning America's obesity epidemic today. The importance of taking a longer historical view on the correlates of diet quality is echoed by nutritionists who have argued that dietary data gathered in the first half of the twentieth century "beg to be recycled into social and historical investigations" (Dirks andDuran 1998, p. 1253).…”
mentioning
confidence: 99%
“…As Nancy Duran points out “many of the earliest dietary researchers were chemists, especially agricultural chemists (2000, p.1882).” Atwater is credited with initiating American household field investigations (now called dietary recalls) on dietary practices during the late 19th century (Dirks & Duran, 1998). As a matter of course, field scientists that kept detailed laboratory records on family households’ dietary patterns inadvertently produced cultural history by recording normative eating patterns and social habits, albeit Atwater’s findings may not have been representative of the entire country.…”
Section: Science and Social Norms In The Late 19th Centurymentioning
confidence: 99%
“…Duran compiled an extensive list of these and other early dietaries (20). Duran supplemented this list and added early cost-of-living studies (23).…”
mentioning
confidence: 99%